The advantages of rime-prompting: a comparative study of prompting methods when hearing children read - Moseley, David; Poole, Sally-Ann (Journal of research in reading, 2001)
Goswami (1999) summarised the evidence supporting the teaching of onset and rime in early reading development. In the present study onset‐rime theory was applied in a randomised controlled trial to the authentic reading task of reading aloud to an adult. Helpers heard Year‐2 children read and responded to miscues and hesitations using one of two prompting procedures. Half of the subjects were prompted using a rime‐prompt approach whereas the other half were told the correct word after five seconds. Progress was measured using word and text‐level tests and the rime‐prompt group performed significantly better than the word‐prompt group at the 5% level. The rime‐prompt method has potential for helping children recognise one‐ and two‐syllable words. It is suitable for use by parents, teachers and other helpers.